Bora Bora Restobar - Carrillo Gaybor, Galo Vinicio (2018)
Today we live in a world that is composed of a social, technological, business and economic dynamism, where the way of satisfying needs must adjust to the tastes and preferences of an increasingly demanding society. The aforementioned becomes the challenge or challenge that any organization must assume when addressing the needs through an offer of goods or services. Entrepreneurship turns out to be a very fashionable term these days, considering it as the capacity to respond to the unmet demand of certain sectors of society, and that provides the opportunity for individuals or groups of individuals to generate alternative solutions in the short term. term.